Factors Associated with Suicidal Ideation in Male Adolescents in the Western Amazon. - Alves da Silva, Thayse; Balthazar Corrêa, Marcelo Tiago; dos Santos Farias, Edson; de Lima Nunes, Laísy; Martins Teodoro, Maycoln Leôni (Paideia (0103863X), 2025)
Males dominate suicide death rates across all age groups. The aim of this study was to investigate suicidal ideation and its associated factors in male adolescents. We assessed a total of 424 adolescents aged between 12 and 18 years, from primary and secondary schools. The instruments used were a sociodemographic questionnaire, the Conceptions of Masculinity Scale/CMS, the Depression, Anxiety and Stress Scale for Adolescents/EDAE-A, and the Beck Scale for Suicide Ideation Scale/BSSI. The prevalence of suicidal ideation was 26.4%, which is considered to be high. The factors associated with the adjusted model were single-parent family structure and shared custody, symptoms of mild and moderate, severe, and extremely severe depression and anxiety. It is recommended that parents and schools be made aware of the need to work on the subject in order to promote prevention in identifying signs of suicidal behavior among adolescents.